SNP 1978–79 - Språkbanken Text (University of Gothenburg, 2024)
Swedish parliament proceedings 1978–1979

Riksdagens snabbprotokoll 1978–1979
SNP 1978–79
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik